Faktor – faktor Penyebab Ibu Post Partum dengan Kejadian Depresi Baby Blues di Klinik PBM Elsi Ramayana Tahun 2023 - Elsi Ramayana; Lisdayanti Simanjuntak; Dina Afriani; Eva Ratna Dewi; Parningotan Simanjuntak (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Postpartum blues is a normal condition, and mothers themselves don't realize that they are experiencing postpartum blues. The aim is to find out the factors that cause post partum mothers to experience baby blues depression at the PBM Elsi Rahayana Clinic in 2023. Pre-Experimental Designs research method. All post partum mothers who gave birth at the PBM Elsi Rahayana Clinic during February – May 2023 were 38 people. Wilcoxon Signed Ranks Test statistical test. The results of the Wilcoxon Signed Ranks Test showed that the p value was <0.05. The research results showed that the majority of respondents with baby blues depression were 36 respondents (94.7%) and the majority of respondents aged < 20 years were 2 respondents (5 .3%). then the results of the Wilcoxon statistical test obtained p (0.001) < 0.005, so it can be concluded that the null hypothesis is rejected, meaning that the majority of respondents with baby blues depression aged 20-35 years were 36 respondents (94.7%) and the minority of respondents aged < 20 years were 2 respondents (5.3%). Based on research results, to determine the factors that cause postpartum mothers to experience baby blues.